Kemampuan Menulis Surat Kelas VII SMP Al-Kautsar Bandar Lampung Tahun Pelajaran 2017/2018 - Octa Ristiana Fareza; Iing Sunarti; Iqbal Hilal (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2018)
The problem discussed in this study is the ability to write a letter to grade VII students of Al-Kautsar Middle School in Bandar Lampung in the 2017/2018 school year. The purpose of this study was to describe the writing ability of class VIII Al-Kautsar Senior High School in Bandarlampung in the 2017/2018 school year in describing parts of letters, choice of words (diction), and the accuracy of the use of spelling. Based on the overall research results in writing letters (part of the letter, choice of words (diction), and the accuracy of spelling use in good categories with an average of 80.6 the ability to write personal letters is in the category (good) with an average value of 80, 6. The ability to write official letters on linguistic aspects is in the category (good) with an average value of 75.5 The linguistic element in writing letters and personal letters is officially in the category (good) with an average value of 78.7.Masalah yang dibahas dalam penelitian ini adalah kemampuan menulis surat siswa kelas VII SMP Al-Kautsar di Bandar Lampung pada tahun pelajaran 2017/2018. Tujuan penelitian ini adalah untuk mendeskripsikan kemampuan menulis siswa kelas VIII SMP Al-Kautsar Bandarlampung pada tahun ajaran 2017/2018 dalam mendeskripsikan bagian-bagian huruf, pilihan kata (diksi), dan keakuratan penggunaan ejaan. Berdasarkan hasil penelitian secara keseluruhan dalam menulis surat (bagian dari surat, pilihan kata (diksi), dan ketepatan penggunaan ejaan dalam kategori baik dengan rata-rata 80,6 kemampuan menulis surat pribadi ada dalam kategori (baik) dengan nilai rata-rata 80,6. Kemampuan menulis surat resmi pada aspek linguistik ada pada kategori (baik) dengan nilai rata-rata 75,5 Unsur linguistik dalam menulis surat dan surat pribadi secara resmi dalam kategori (baik) dengan nilai rata-rata 78,7.Kata kunci: kemampuan menulis huruf, bagian surat, bahasa